BETWEEN APPARITION AND VANISHING: AESTHETIC THRESHOLDS IN THE WORK OF OSCAR MUÑOZ - Flor Ángel Rincón Muñoz (Pensamiento Palabra y Obra, 2014)
This article intends a reading of the artistic production of the Colombian artist Óscar Muñoz (1951). For so doing, we start from his early works -and from a psychoanalytic perspective- to focus on the analysis of apparitionand vanishing, concepts which are undertaken chiefly from the viewpoint of Martin Seel (1954) and Paul Virilio (1932). In this way, an alternative reading of the aesthetic and significant processes found in the works of Muñoz is proposed.